2004
DOI: 10.1128/aem.70.12.7574-7577.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of Cryptosporidium Species Infecting Fur-Bearing Mammals Differ from Those of Species Infecting Humans

Abstract: Of 471 specimens examined from foxes, raccoons, muskrats, otters, and beavers living in wetlands adjacent to the Chesapeake Bay, 36 were positive for five types of Cryptosporidium, including the C. canis dog and fox genotypes, Cryptosporidium muskrat genotypes I and II, and Cryptosporidium skunk genotype. Thus, fur-bearing mammals in watersheds excreted host-adapted Cryptosporidium oocysts that are not known to be of significant public health importance.The enteric parasites in the genus Cryptosporidium can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 21 publications
3
65
2
Order By: Relevance
“…These results highlight the importance of genotyping analysis as there are significant differences in the zoonotic risk between genotypes and therefore hazard analysis critical control point analysis based on data from microscopy alone could significantly overestimate the risk of human cryptosporidiosis and giardiasis from sheep-derived protozoan contamination of catchments, effluents, and abattoirs. This is further supported by recent studies in the United States and Australia which reported that mammals and marsupials in watersheds excreted host-adapted Cryptosporidium oocysts not known to be of significant public health importance and that the potential role of wildlife in the transmission of human Cryptosporidium infection had been overestimated (30,43). This is also in agreement with the previous finding of only wildlife Cryptosporidium genotypes in runoff (storm water) in feral areas in the United States (40).…”
Section: Discussionsupporting
confidence: 82%
“…These results highlight the importance of genotyping analysis as there are significant differences in the zoonotic risk between genotypes and therefore hazard analysis critical control point analysis based on data from microscopy alone could significantly overestimate the risk of human cryptosporidiosis and giardiasis from sheep-derived protozoan contamination of catchments, effluents, and abattoirs. This is further supported by recent studies in the United States and Australia which reported that mammals and marsupials in watersheds excreted host-adapted Cryptosporidium oocysts not known to be of significant public health importance and that the potential role of wildlife in the transmission of human Cryptosporidium infection had been overestimated (30,43). This is also in agreement with the previous finding of only wildlife Cryptosporidium genotypes in runoff (storm water) in feral areas in the United States (40).…”
Section: Discussionsupporting
confidence: 82%
“…data), but the source is unknown. Since many isolates have yet to be found in humans and although little is actually known about them, they are assumed to be insignifi cant to public health (6,15). The importance of unusual genotypes in humans who seek treatment for diarrheal disease warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Caution needs to be used when extrapolating molecular data from water samples to concretely determine host sources of contamination. In studies that examine the host specificity of Cryptosporidium parasites, there is a direct association between the host being studied and the fecal material used for typing parasites (30,37,55). This direct association does not exist for isolates from water samples.…”
Section: Discussionmentioning
confidence: 99%